Heterogeneous catalytic reaction of glycerol with acetone for solketal production - Sulistyo, Hary; Hapsari, Indri; Budhijanto; Sediawan, Wahyudi Budi; Rahayu, Suprihastuti Sri; Azis, Muhammad Mufti (MATEC web of conferences, 2019)
The rapid growth of biodiesel industries has also increased the production of glycerol as side product. Without proper treatment, glycerol may cause serious problem for the environment. Glycerol can be reacted with acetone to produce solketal as a fuel additive. The aim of this research was to study the glycerol ketalization with acetone using Amberlyst-15 as catalyst. Experiments were undertaken in a batch reactor. A set of experiment was conducted at varying temperature (35 to 60 o C), initial mole ratio of acetone to glycerol (2 – 6) and catalyst loading (1,3,5 and 7% w/w). Sample was analyzed every 30 minutes. The results showed that optimal condition was achieved at temperature of 60 °C, initial mole ratio of acetone to glycerol of 3, and the catalyst load of 3%. The highest glycerol conversion achieved was 87.41 % at 60 o C for 3 hours reaction. The Pseudo Steady State Hypothesis (PSSH) has been developed as r net =k 4 .C G .C AC /1+k 5 .C G . Parameter estimation of k 4 and k 5 were evaluated from experimental data at various temperatures. It appears that the model predicted the experimental data well at high conversion (above 80 min) and showed relatively poor prediction below 80 min.